Portfolio model for decision process concerning organizational change management - Slabospitskaya, O.A. (Інститут програмних систем НАН України, 2017)
The model is proposed for integrated decision process concerning innovative organizational change management to sustainable realization of benefits – the changes’ outcomes expected by some stakeholders and acceptable for the others. The process is represented with cycles of benefits realization through target portfolios being systems of deciding and implementing projects jointly managed (that model benefitled decisions making and implementing) in ontology-based information environment. Additional quality model and the system of quality audit operations based on it are elaborated for the modelled decision process. All the models proposed jointly support expected internal decision quality for its implementers as well as nonbenefitial decisions avoidance and benefits nonachieving risks management – for decision makers.